Adjustments Made to the Emergency CurriculuM - Nurhayati Ganinda (Jetlal, 2022)
Among the teachers’ duty is to fulfill the mandatory material in a curriculum. Yet the Pandemic made it nearly impossible for teachers to carry out their duty to fulfill it. The time, the learning platform, the number of material, and other countless factors hinder its’ fulfillment. Thus the government issued a decree of Emergency Curriculum to address this problem. This study aims to see the difference between the Revised K13 Curriculum which is used prior to the Global Pandemic Covid-19 and the Emergency Curriculum which is issued by the Ministry of Education during the Covid-19 Pandemic. This research used document analysis method, and the source of data is the attachment of Decree of The Minister of Education and Culture of The Republic of Indonesia No. 719/P/2O2O about Curriculum Implementation Guidelines in Education Units under Special Conditions. The attachment consist of core competencies and basic competencies for all level of education, and only attachment for middle and high school level of English subject will be analyzed. The results of the analysis show that there are reduction as much as 57% of the middle school level material, and as much as 40% reduction of the high school level material. Specifically the material for the 7th grade junior high school level is reduced as much as 35%, the 8th grade junior high school as much as 67%, and the 9th grade junior high school as much as 58%. Whereas for 10th grade senior high school level there is 33% reduction, for 11th grade there is 47% reduction, and for 12th there is 41% reduction. The highest reduction is given to grammar material which is reduced by 75% in all grade level, the second most reduced is short functional text by 67% reduction, and followed by long functional text with the least reduction of 11%.